A review of Ellescus (Coleoptera: Curculionidae) in North America: new species and synonyms revealed through integrative taxonomy. (12th April 2023) - Lewis, Jake H.; Anderson, Robert S.
Abstract: A combination of morphological and molecular techniques were used to revise the genus Ellescus Dejean, 1821 (Coleoptera: Curculionidae: Ellescini) in North America. Four valid species of Ellescus are documented from the Nearctic Region. These are the widespread, hypervariable E. ephippiatus (Say, 1831), the Holarctic E. bipunctatus (Linnaeus, 1758) (of which E. borealis (Carr, 1920) new synonym is found to be a new junior synonym), the west coast endemic E. californicus (Casey, 1885) (resurrected from synonymy with E. ephippiatus (Say, 1831)), and the temperately distributed E. michaeli new species . A neotype is designated for E. bipunctatus . The European species, E. scanicus (Paykull, 1792), is determined to have been erroneously reported from North America. An illustrated identification key, distributional data, and DNA sequences ( CO 1, ITS 2) are provided to facilitate identification of the Ellescus species in North America. Notably, CO 1 failed to delineate E. ephippiatus and E. michaeli, but the faster-evolving ITS 2 reliably separated these taxa, further supporting the use of multiple markers in taxonomic studies and the utility of ITS 2 in weevil species delineation.